Teknologi bercocok tanam di lahan sempit di Kecamatan Tempe Kabupaten Wajo - Arsad Bahri; Adnan Adnan; Sultan Sultan (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Mattirotappareng is one of the villages located inTempe District, Wajo Regency. The progress of developmentin Wajo Regency is not in line with the progress of theknowledge of the people, especially the knowledge ofinnovation in agriculture. So that, the community is lacks newknowledge about crop cultivation to improve the level ofcommunity welfare. The problem faced is the limited land forfarming. Planting needs to be accompanied by the latestaccuracy and innovation in accordance with the developmentof technology and science. Verticultural technique is anopportunity as well as a challenge that can be used to improveagricultural yields in the area of Mattirotappareng Village,Tempe District. Verticulture system is the result of researchconducted in the Department of Biology, Faculty ofMathematics and Natural Science, Universitas NegeriMakassar. The research has been carried out and based ontechnology products should be downstream so that it can beutilized by the community. Dissemination of the results of thisstudy can be done by socialization, counseling/training, andmentoring. With this program, it is expected that the limitedland will no longer be a problem of farming for the people inMattirotappareng Village.